Welcome back to Junkspace! Performing infinity while confined in lockdown. Issue 4 (26th December 2020) - Rodger, Johnny
Abstract : For months we have been locked out of Junkspace. So, who's complaining? Confined to domestic spaces, #stayhome has given many of us a forced opportunity to rethink the type of spaces that are not only functional and useful, but that make us feel comfortable. Our own residential arena may have felt restrictive and even – for some – oppressive at times, but who would say that they truly missed their daily passage through the endlessly stale air of check-in desks, departure gates, and duty frees at the airport; the epic journeys through low ceiling corridors and passageways of railway terminals and subway stations; and the blinding hallucinatory proliferation of brands and franchises in malls…?